2016
DOI: 10.1103/physrevlett.117.217203
|View full text |Cite
|
Sign up to set email alerts
|

Magnon Spin Nernst Effect in Antiferromagnets

Abstract: We predict that a temperature gradient can induce a magnon-mediated spin Hall response in an antiferromagnet with non-trivial magnon Berry curvature. We develop a linear response theory which gives a general condition for a Hall current to be well defined, even when the thermal Hall response is forbidden by symmetry. We apply our theory to a honeycomb lattice antiferromagnet and discuss a role of magnon edge states in a finite geometry.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
201
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(207 citation statements)
references
References 51 publications
2
201
1
3
Order By: Relevance
“…This effect does not rely on the presence of time-reversal symmetry breaking, unlike the thermal Hall effect (thermal analog of the Hall effect). Several recent papers (Cheng, Okamoto, and Xiao, 2016;Zyuzin and Kovalev, 2016) demonstrated the spin Nernst effect in models of honeycomb lattice magnets with Dzyaloshinski-Moriya interactions.…”
Section: A Thermally Induced Spin Currentsmentioning
confidence: 99%
“…This effect does not rely on the presence of time-reversal symmetry breaking, unlike the thermal Hall effect (thermal analog of the Hall effect). Several recent papers (Cheng, Okamoto, and Xiao, 2016;Zyuzin and Kovalev, 2016) demonstrated the spin Nernst effect in models of honeycomb lattice magnets with Dzyaloshinski-Moriya interactions.…”
Section: A Thermally Induced Spin Currentsmentioning
confidence: 99%
“…1 (b). Spins of length S on each bipartite sublattice, denoted by A and B, satisfy 60,61,66 S A = −S B = Se z in the ground state. The magnet is described by the following spin Hamiltonian, 42,43 …”
Section: Topologically Trivial Afmentioning
confidence: 99%
“…[13], we developed it further into the magnonic 'quantum' Hall effect and appropriately defining the thermal conductance for bosons, we found that the magnon Hall conductances in such topological FMs obey a Wiedemann-Franz 50 (WF) law for magnon transport 4,47 . In this paper, motivated by the recent experimental 51 demonstration of thermal generation of spin currents in AFs using the spin Seebeck effect [52][53][54][55][56][57][58][59] and by the report [60][61][62] of the magnonic spin Nernst effect in AFs, we develop Ref. [46] further into the AF regime [42][43][44][45]63,64 and propose a magnonic analog of the QSHE [31][32][33][34][35]39,40 for edge states that carry helical edge magnons [ Fig.…”
mentioning
confidence: 99%
“…Refs. [57,58] have theoretically proposed magnon spin Nernst effects in antiferromagnets [59][60][61] .…”
Section: Introductionmentioning
confidence: 99%